Comparison of Educational Theories: Perspectives of Carol Dweck and Howard Gardner in Developing Individual Potential - Prodyanatasari, Arshy; Prayitno, Mustofa Aji; Leuwol, Ferdinand Salomo; Aminah, Siti; Maskur, Maskur (ANTHOR: Education and Learning Journal, 2023)
This research aims to compare Carol Dweck's Growth Mindset Theory and Howard Gardner's Multiple Intelligences Theory in the context of developing individual potential. The study utilizes literature review and comparative analysis as the research method to compare the two theories. In the pursuit of optimizing individual potential, the growth mindset emphasizes the importance of a developing mindset, viewing failures as opportunities for learning, and creating a supportive learning environment. On the other hand, multiple intelligences theory acknowledges the diversity of intelligences and advocates for the development of all types of intelligence in education. In inclusive modern education, the application of both theories can motivate students to grow and learn, develop self-confidence, and optimize their potential in various areas of intelligence. Through this approach, modern education can create a stimulating environment, facilitate holistic development, and produce individuals who are prepared to face future challenges. By understanding the differences and similarities between these two theories, education can adopt an inclusive approach that focuses on the full development of each individual's potential, ensuring that students are empowered to achieve academic success and optimal personal growth.